Exploring economic status of the elderly in Peninsular Malaysia using net flow and net worth - Masud, Jariah; Haron, Sharifah Azizah; Gikonyo, Lucy Wamuyu (Center for Promoting Ideas, 2012)
Economically, as people reach retirement and start drawing on their savings and accumulated stocks of wealth, they may experience a lot of uncertainty as a result of lack of proper planning. In the developing world, elderly people are consistently among the poorest and most marginalized (Help Age International, 2000). This study sought to examine the economic status of the elderly using net flow and net worth. Four aspects of focus are Income, expenditure, assets and liabilities. The study also explored the Economic Status of elderly using four typologies (Positive net worth and Positive net flow, Negative net worth and Positive net flow, Positive net worth and Negative net flow, Negative net worth and Negative net flow). A total of 1841 elderly males and females from Peninsular Malaysia participated in the study. The findings revealed that elderly males and females differed in their economic status as indicated by their net flow and net worth. A significant proportion of both elderly males and females had positive net worth and net flow values.